HUMAN RESOURCE MANAGEMENT IN LOCAL STATE GOVERNMENT BODIES - Abdurahmanova Gulnora Kalandarovna (Labor economics and human capital, 2023)
In this article, the author discusses the scope and relevance of human resource management and how human resource management is important to the success of local government agencies. The article focuses on the elements of human resource management consisting of tasks and skills necessary for the development of an effective human resource management system in local government bodies. In the study, the important functions of human resources management in local government bodies and theoretical and practical aspects of some of the problems that arise in it are emphasized. This study also surveyed the opinions of human resource management professionals at the local government level to determine the importance of a number of functions and practices in human resource management practices today.